Quantitation of Tenofovir and Emtricitabine in Dried Blood Spots (DBS) with LC-MS/MS - Zheng, Jia-Hua (2013)
A reversed-phase high performance liquid chromatographic (LC), tandem mass spectrometry (MS/MS) assay for the determination of tenofovir (TFV) and emtricitabine (FTC) in dried blood spots (DBS) from human whole blood was developed and validated. Whole blood samples were spotted, dried, and a 3mm punch was extracted with methanol for analysis by LC-MS/MS utilizing stable isotope labeled internal standards. The assay was validated over the range of 2.5ng/mL to 1,000ng/mL for TFV and 2.5ng/mL to 5,000ng/mL for FTC. The method was accurate (within ± 15% of control) and precise (coefficient of variation ≤ 15%) for hematocrit concentrations ranging from 25% to 76%; using edge punches versus center punches; and spot volumes of 10µL to 50µL. Analytes were stable for five freeze/thaw cycles and up to 6 days at room temperature, whereas long-term storage required −20°C or −80°C. Comparison of TFV and FTC in DBS versus plasma yielded r(2) ≥ 0.96, indicating that DBS can be used as a plasma alternative for pharmacokinetic analyses in vivo.